2014
DOI: 10.5539/ijel.v4n1p84
|View full text |Cite
|
Sign up to set email alerts
|

A Review of EFL Arab Learners’ Language: Pitfalls and Pedagogical Implications

Abstract: Nonetheless, that there are distinguished, qualified, specialized and experienced teachers; in addition to good overall designing and planning; comprehensive and purposive curriculum, integrated textbooks, but the achievement is still below the expectations of all who are concerned with English language teaching in the Arab world. The current study is set out to review kinds of pitfalls encountered by EFL Arab Learners at the tertiary level in the use of the most three problematic syntactic/semantic sub-catego… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…To say it differently, L1 interference affects L2 learning and practicing, leading to committing errors of such a kind. Supporting this idea is Tahaineh (2014) who concluded that the majority of ESL/EFL Arab students made enormous errors in using the articles in English due to the interference of their L1. An additional reason behind this error could be linked to what is called intra-lingual transfer, more specifically; incomplete application of a rule.…”
Section: Results Pertaining To the Second Question Of The Researchmentioning
confidence: 79%
“…To say it differently, L1 interference affects L2 learning and practicing, leading to committing errors of such a kind. Supporting this idea is Tahaineh (2014) who concluded that the majority of ESL/EFL Arab students made enormous errors in using the articles in English due to the interference of their L1. An additional reason behind this error could be linked to what is called intra-lingual transfer, more specifically; incomplete application of a rule.…”
Section: Results Pertaining To the Second Question Of The Researchmentioning
confidence: 79%
“…The great number of prepositions, along with their dissimilar meaning in both Arabic in English, can be an obstacle for EFL learners to learn this item of the language. For instance, learners tend to translate the Arabic preposition system into English which results in making errors in the use of the English prepositions (Mourssi & Al Hilali, 2015;Tahaineh, 2014). In addition, English and Arabic possessive noun phrases are identically structured, however, Arab learners sometimes make errors in the use and position of ''s' (Qasim, 2013).…”
Section: Learners' Common Syntactic and Morphological Writing Errorsmentioning
confidence: 99%
“…For example, they would write "I am interested with it" instead of "I am interested in it." Such mistakes occur because Arabic prepositions follow different rules and as mentioned earlier in this article and Arab learners would use correct prepositions only if they had an equivalent in their native language or else they would omit or use wrong prepositions (Tahaineh, 2010).…”
Section: Target Language Errors Due To Mother Tongue Interferencementioning
confidence: 78%
“…Pedagogically, these learners could be taught to be careful when they make such transfers. They can be made aware of positive and negative transfers while teaching grammar (Tahaineh, 2010). Thus, identification of the problem could lead to designing new pedagogical strategies for teaching syntax to Arab learners and creating awareness in them to avoid such errors.…”
Section: Efl Teacher's Role In Creating Awareness In Areas Of Differementioning
confidence: 99%
See 1 more Smart Citation